محددات التجربة الصينية في تحدياتها للعولمة الثقافية - لخضاري محمد حسني (المسيلة, 2023)
استطاعت الصين عبر نموذج تنموي فريد أن تحقق نموا اقتصاديا وسياسيا ... هائال سمح لها أن تصنع لنفسها مكانة بين القوى الكبرى وأن تتحول إلى قطب دولي مؤثر في تفاعالت السياسة الدولية وهذا في ظل تراجع " غربي - أمريكي " ، أين أوارت عدة دراسات استراتيجية أن النظام الدولي يتجه نحو عصر تكون فيه الصين إلى جانب الواليات المتحدة األمريكية قوة مهيمنة عالميا . األمر الذي تسبب في قلق غربي من فقدان ريادته وهيمنته على العالم ، خاصة في ظل وجود اختالفات ثقافية عميقة مع الصين ) بصفتها حضارة ورقية ( ، األمر الذي استدعى من الغرب العمل على كبح هاته النهضة والصعود الصيني ، عبر احتوائه بوتى الطرق كالعولمة الثقافية ، التي تهدف ضمن أهدافها الغير معلنة إلى تفتيت المجتمعات وتفكيكها عبر نور الفرقة بين مختلف القوميات " اللغوية ، العرقية ، الدينية ... الخ " ، إضافة إلى نور مختلف الظواهر السلبية المحطمة للمجتمعات مثل : اإلباحية ، المثلية ، المخدرات ... الخ . غير أن الصين تمكنت لحد الساعة من التصدي لهاته الهجمات نظرا لتمتعها بأسس ومقومات متينة ) اقتصادية ، سياسية ، اجتماعية ، ثقافية ... الخ ( ، األمر الذي جعلها نموذجا حضاريا ناجحا يقتدى به . - اللغةاإلجنليزية : Study summary: Through a unique development model, China was able to achieve tremendous economic and political growth that allowed it to carve out a position for itself among the major powers and to turn into an influential international pole in the interactions of international politics, and this is in light of the "Western-American" decline. The international community is heading towards an era in which China, along with the United States of America, will be a global dominant power. This caused Western concern about losing its leadership and hegemony over the world , especially in light of the existence of deep cultural differences with China (as an eastern civilization) , Which necessitated the West to work to curb this Chinese renaissance and rise by containing it in various ways, such as cultural globalization, which aims, among its undeclared goals, to fragment societies and dismantle them by spreading disunity between different nationalities, "linguistic, ethnic, religious...etc " in addition to spreading Various negative phenomena that destroy societies, such as: pornography, homosexuality, drugs...etc. However, China has so far been able to confront these attacks due to its solid foundations and ingredients (economic, political, social, cultural, etc.) , Which made it a successful civilized model to follow
Keywords: محددات التجربة الصينية - تحدياتها - العولمة الثقافية